Spectroscopic near-infrared photodetectors enabled by strong light-matter coupling in (6,5) single-walled carbon nanotubes - Mischok, Andreas; Lüttgens, Jan; Berger, Felix J.; Hillebrandt, Sabina; Tenopala-Carmona, Francisco; Kwon, Seonil; Murawski, Caroline; Siegmund, Bernhard; Zaumseil, Jana; Gather, Malte C. (The journal of chemical physics, 2020)
Strong light-matter coupling leads to the formation of mixed exciton-polariton states, allowing for a rigorous manipulation of the absorption and emission of excitonic materials. Here, we demonstrate the realization of this promising concept in organic photodetectors. By hybridizing the E11 exciton of semiconducting (6,5) single-walled carbon nanotubes (SWNTs) with near-infrared cavity photons, we create spectrally tunable polariton states within a photodiode. In turn, we are able to red-shift the detection peak that coincides with the lower polariton band. Our photodiodes comprise a metal cavity to mediate strong coupling between light and SWNTs and utilize P3HT and PC70BM as the electron donor and acceptor, respectively. The diodes are formed either via mixing of SWNTs, P3HT, and PC70BM to create a bulk heterojunction or by sequential processing of layers to form flat heterojunctions. The resulting near-infrared sensors show tunable, efficient exciton harvesting in an application-relevant wavelength range between 1000 nm and 1300 nm, with optical simulations showing a possible extension beyond 1500 nm.
Gesehen am 18.01.2021